RAB5C, a new mRNA binding target of HuR, regulates breast cancer cell proliferation. (8th December 2022) - Wang, Zhenzhen; Li, Fang; Zhang, Huahua; Hu, Xiaoyi; Chen, Yanke; Huang, Chen
Abstract: The posttranscriptional control of gene expression mediated by RNA‐binding proteins (RBPs) is essential to determine tumor cell fate. HuR is an RBP with increased expression in various cancer types. This study aimed to clarify the regulatory mechanism of HuR's contribution to breast cancer (BC) cell proliferation by inducing RAB5C expression. First, we analyzed the expression level of HuR and RAB5C in BC tissues and cell lines by immunohistochemistry, qRT‐PCR, and western blot. Next, to further investigate the effect of HuR on RAB5C expression, we used short hairpin RNAs (shRNAs) to silence endogenous HuR expression in BC cell lines MCF7 and MDA‐MB‐231. The binding site of RAB5C mRNA and HuR was confirmed by RNA immunoprecipitation. Finally, the function of RAB5C was investigated using flow cytometry, colony formation, and MTT assays. We found that the expression of HuR and RAB5C was significantly upregulated in BC tissues and MCF‐7 and MDA‐MB231 cell lines. Importantly, RAB5C mRNA stability was increased through binding of HuR to its 3′UTR. Inhibition of HuR expression using shRNA decreased RAB5C mRNA, suggesting that HuR plays a role in regulating RAB5C expression level. In addition, suppression of RAB5C expression reduced BC cell growth. These results suggest RAB5C functions as an oncogene in BC cells, HuR promoted BC cell survival by facilitating RAB5C expression. Our findings suggest that HuR and RAB5C play important roles in BC cell survival.